Biodiversity scientific expedition to Kuala Terengganu 2016 - Asli, Millaa Armilla (Universiti Teknologi MARA, Sarawak, 2016)
First of all, I would like to thank UiTM Sarawak for giving a grant of RM7,500 to 25 students from AS1204A for an academic visit to Kuala Terengganu from 20 April to 23 April 201 6. On the first day, we started our journey from the Kuching International Airport to the Kuala Lumpur International Airport 2 and finally landed at the Sultan Mahmud Kuala Terengganu Airport at 4.30 pm. We stayed at Universiti Teknologi MARA Kuala Terengganu throughout the trip.